Effects of different nitrogen levels on tritrophic interaction of cabbage (Brassica oleraceae L. var. capitata), diamondback moth (Plutella xylostella L.) and Cotesia plutellae Kurdjumov - Othman, Siti Nur Fatimah (2021)
Nitrogen (N) fertilizer is crucial mineral nutrition for the growth and development of cabbage (Brassica oleraceae L. var. capitata). However, N fertilizer also affect the susceptibility of plant to the diamondback moth (DBM). Cotesia plutellae is one of the alternative methods to minimize the DBM population densities on plants. Understanding tritrophic interaction is vital to improve plant health and better integrated pest management (IPM). Thus, this study was investigated the effect of different N levels on tritrophic interaction of cabbage, DBM and Cotesia plutellae. The experiment was conducted in the glasshouse to investigate the effect of N fertilizer on growth and performance of cabbage using Randomized Complete Block Design (RCBD) with five replications. The plants were applied 100 ml with different level of N (50 mg/L;100 mg/L; 150 mg/L; 200 mg/L and 300 mg/L) on week 2 and 4 after transplanting. Cabbage was harvested at week 6, 9 and 12 to measure the leaf area, dry weight of plants, macronutrients (N, P, K) and glucosinolate (GSL) content. The studies of DBM development and parasitism of C. plutellae on DBM were assessed in cages using RCBD with the 6-week-old of plant. The first study shows the root length, leaves area and dry weight of leaves and root given significantly different when applied with highest N treatment. At week 6, N content in leaves was higher compared to the week 9 and 12. It was found the GSL contents is higher on cabbage at week 6. Thus, for second study, the DBM larva were fed with 6th week old plant with different N levels. Larva fed highly N showed shorten development period with 4.38 days. In third study, DBM larva were fed with different level of N were released for study C. plutellae in choice and no-choice test. The results shown there is no significantly different between choice and no-choice treatment. However, the higher parasitism (50.65%) and (42.61%) recorded of C. plutellae on DBM was shown when infested on highly N content for choice and no-choice test at respectively. Hence, N fertilizer promoting growth and development of cabbage. Simultaneously, DBM development were grown faster when fed higher and percentage of parasitism were greatest for DBM larvae feeding on plants that had received higher N in choice and no-choice test.